ANALISIS PERBANDINGAN PENERAPAN STATIC ROUTING PADA IPV4 DAN IPV6 - Ulfa, Maria ; Fatoni, Fatoni (Universitas Bina Darma, 2017)
Static routing is a Router that has a static routing table that is configured manually by network administrators. Static routing is the simplest routing setting that can be done on a computer network. IP Addresss version 6 is the latest version in Internet protocol based computer networking protocol, which was created to provide solutions to the main problems in IPv4, namely the limitation of addressing capacity. IPv4 is only able to reach as many as 4 octets with each octet maximum of 255 pieces of computer in it, so it can be said that for all computers currently able to handle numbers of 4 billion. In IPv6 there are 16 Octet with one octet capable of loading maximum 255 pieces of computers and other connected devices that can be accommodated is about 3.4 trillion. Therefore the authors will conduct a comparison study analysis of the use of IPv4 and IPv6 to see the performance of both in the implementation of static routing, parameters in the test Throughput, Delay and Packet loss. Keywords: IPv4, IPv6, Static Routing.